Franz Joseph Haydn and the Five-Octave Classical Keyboard: Registral Extremes, Formal Emphases and Tonal Strategies - MacKay, James (Canadian University Music Review / Revue de musique des universités canadiennes, 2003)
The Classical keyboard in its various forms (harpsichord, clavichord and fortepiano) typically had a modest five-octave range (FF–f3) prior to ca. 1800. This essay examines how this range influenced the tonal shape of Joseph Haydn's keyboard music written after 1765. The author explores how Haydn used registral extremes to emphasize major formal junctures, cadences and modulations. Finally, he explores how the presence or absence of the keyboard's extreme pitches contributes to key character, examining the different contexts in which Haydn uses them in three tonalities: D minor, C major and A major.